Identification of hierarchy of dynamic domains in proteins: comparison of HDWA and HCCP techniques - Yesylevskyy, S.O. (Вiopolymers and Cell, 2010)
Aim. There are several techniques for the identification of hierarchy of dynamic domains in proteins. The goal of this work is to compare systematically two recently developed techniques, HCCP and HDWA,on a set of proteins from diverse structural classes. Methods. HDWA and HCCP techniques are used. The HDWA technique is designed to identify hierarchically organized dynamic domains in proteins using the Molecular Dynamics (MD) trajectories, while HCCP utilizes the normal modes of simplified elastic network models. Results. It is shown that the dynamic domains found by HDWA are consistent with the domains identified by HCCP and other techniques. At the same time HDWA identifies flexible mobile loops of proteins correctly, which is hard to achieve with other model-based domain identification techniques. Conclusion. HDWA is shown to be a powerful method of analysis of MD trajectories, which can be used in various areas of protein science. Існує кілька методів для визначення ієрархії динамічних доменів у білках. Мета даної роботи полягала у проведенні систематичного аналізу двох нещодавно створених методів – HCCP та HDWA – на основі тестового набору білків з різних структурних класів. Методи. Використано методи HDWA та HCCP. Перший розроблено для визначення ієрархії доменів з використанням траєкторій молекулярної динаміки, тоді як другий грунтується на нормальних коливаннях спрощеної ела- стичної моделі білка. Результати. Встановлено, що динамічні домени, знайдені методом HDWA, добре узгоджуються з доменами, визначеними методом HCCP та із застосуванням інших підходів. У той же час HDWA правильно визначає рухливі петлі в білках, чого важко досягти іншим способом. Висновки. Показано, що HDWA є потужним методом аналізу траєкторій молекулярної динаміки для багатодоменних білків. Существует несколько методов для определения иерархии динамических доменов в белках. Цель данной работы состояла в систематическом анализе двух недавно созданных методов – HCCP и HDWA – на основе тестового набора белков из разных структурных классов. Методы. Использованы методы HDWA и HCCP. Первый разработан для определения иерархии динамических доменов с использованием траекторий молекулярной динамики, тогда как второй основан на нормальных колебаниях упрощенной эластичной модели белка. Результаты. Установлено, что динамические домены, найденные методом HDWA, хорошо соответствуют доменам, определенным методом HCCP и с применением других подходов. В то же время HDWA правильно определяет подвижные петли в белках, чего трудно достичь другим способом. Выводы. Показано, что HDWA является мощным методом анализа траекторий молекулярной динамики для многодоменных белков.